Peran Pembelajaran IPS Dalam Membentuk Karakter dan Budaya Bangsa Pada Anak Sekolah Dasar - Elza Amalia Salsya Bani; Moch Lucky Winandar; Tin Rustini (Departement of Mathematics Education, 2023)
Social studies learning has an important role in the formation of student character. However, Social Studies learning in the formation of students' character is certainly not a problem easy, it takes continuous struggle to produce good results in accordance with the goals of national education. Social studies learning has something in common with character education, both of which have the goal of making students as good citizens, care about social problems, the existing environment, and also share a high sense of nationality.